Medicinal Plant Images - Cock, Ian E (Pharmacognosy Communications)
Moringa oleifera Lam. (commonly known as horse radish tree, drumstick tree, tree of life) is a fast growing, drought resistant tree which has widespread cultivation in tropical and subtropical regions globally. It is particularly common in northwest regions of India, from where it is believed to have originated, although it has been naturalised worldwide. Most parts of the tree are edible and are consumed as nutritious vegetables.1 The leaves, fruit, seeds, flowers, bark and sap are also incorporated into several traditional medicine systems and several antimicrobial studies have reported growth inhibitory activity for various parts of M. oleifera against a range of pathogens. One study reported that aqueous, acetone and ethanolic leaf extracts displayed antibacterial activity comparable to that of ciprofloxacin, cotrimoxazole and chloramphenicol.2 Another study reported potent inhibition of the growth of a broad bacterial panel by M. oleifera leaf juice.3 Shigella dysenteriae, Bacillus cereus, Escherichia coli and Salmonella typhi were considered to be especially susceptible to seed extract.4 However, the published literature is contradictory, with several studies reporting little or no inhibitory activity against many of the same bacterial species. A recent study reported that M. oleifera leaf solvent extracts were completely ineffective against multiple species of Bacillus, Streptococcus, Klebsiella and Pseudomonas,5 where previously potent activity was reported.4 Whilst the latter study5 did report activity against some bacterial species previously reported to be highly susceptible to M. oleifera (E. coli, S. aureus) in other studies, the concentrations required to achieve growth inhibition (≥5 mg/mL) in that study indicated only low antibacterial activity. A recent study reported that whilst M. oleifera extracts had moderate antibacterial activity against a panel of bacterial pathogens, combinations of the extracts with conventional antibiotics were substantially more effective, with the extracts potentiating the activity of some antibiotics substantially in excess of four fold, even against bacterial strains otherwise resistant to those antibiotics.6